2017
DOI: 10.1111/irv.12469
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of influenza A(H1N1)pdm09 viruses isolated from Nepalese and Indian outbreak patients in early 2015

Abstract: We characterized influenza A(H1N1)pdm09 isolates from large‐scale outbreaks that occurred in Nepal and India in early 2015. Although no specific viral features, which may have caused the outbreaks, were identified, an S84N substitution in hemagglutinin was frequently observed. Chronological phylogenetic analysis revealed that these Nepalese and Indian viruses possessing the S84N substitution constitute potential ancestors of the novel genetic subclade 6B.1 virus that spread globally in the following (2015/16) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 10 publications
2
11
1
Order By: Relevance
“…In NA phylogeny, amino acid substitutions V13I, I34V, and I314M were found in all Myanmar strains. These substitutions were also detected in Indian and Nepalese A(H1N1) pdm09 outbreak strains in early 2015, which suggests the coevolution of HA and NA [16]. According to our investigation (unpublished data), influenza A(H3N2) and B viruses, which were the predominant circulating strains in Myanmar during 2016, could be a possible reason for this big outbreak of A(H1N1)pdm09 and it may be responsible for the reduced herd immunity against A(H1N1)pdm09, when the new 6B.1 clade virus was introduced in Myanmar in 2017.…”
Section: Plos Onementioning
confidence: 85%
See 2 more Smart Citations
“…In NA phylogeny, amino acid substitutions V13I, I34V, and I314M were found in all Myanmar strains. These substitutions were also detected in Indian and Nepalese A(H1N1) pdm09 outbreak strains in early 2015, which suggests the coevolution of HA and NA [16]. According to our investigation (unpublished data), influenza A(H3N2) and B viruses, which were the predominant circulating strains in Myanmar during 2016, could be a possible reason for this big outbreak of A(H1N1)pdm09 and it may be responsible for the reduced herd immunity against A(H1N1)pdm09, when the new 6B.1 clade virus was introduced in Myanmar in 2017.…”
Section: Plos Onementioning
confidence: 85%
“…According to the phylogenetic analysis, the 2017 Myanmar influenza A(H1N1)pdm09 strains belonged to clade 6B.1 and were closely related to the strains that circulated in India and other countries during the same period. India reported several outbreaks and severe cases caused by influenza A(H1N1)pdm09 of Clade 6B and 6B.1 during 2015-2017 [16][17][18][19][20]31]. We suspect the possibility of transmission from India or other countries situated to the west of Myanmar because early cases of this outbreak were reported from Chin State, which shares its western border with Bangladesh.…”
Section: Plos Onementioning
confidence: 97%
See 1 more Smart Citation
“…Severe and fatal outbreaks occurred in early 2015 in Nepal and India [42]. A study in Taiwan showed patients with laboratory-confirmed H1N1pdm 6B, 6B.1 and 6B.2 in 2013-14 and 2015-16 had higher risk for influenza-related complications compared to patients from seasons where 6B, 6B.1 and 6B.2 viruses did not dominate [43].…”
Section: Discussionmentioning
confidence: 99%
“…In our country, between 2015 and 2016 years a mild outbreak of H1N1 viruses has emerged, and lethal cases were detected as seen in Nepal and India in early 2015 (16). During the admission to the hospital, a prediction for severity and mortality should be assessed in patients with H1N1 pneumonia since some factors may have resulted in death.…”
Section: Discussionmentioning
confidence: 99%